2023
DOI: 10.1002/jsfa.12485
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Robusta coffee aroma with l‐leucine powder

Abstract: L-leucine powder (LP) were added to improve the aroma of Robusta coffee beans. Treatment was a short soaking (M1) or spraying procedure (M2), then LP was added at varying levels up to 3% (w/w). All samples were roasted (240 °C/15 min) and extracted using an espresso machine. Volatile compounds were analysed by solid-phase microextraction−gas chromatography−mass selective detection. Thirty volatile compounds (6 pyrroles, 8 pyrazines, 3 phenols, 9 furans, 2 ketones, 2 aldehydes) were analysed. In 15 coffee sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to previous studies, Robusta showed considerably higher concentrations of pyrazines than Arabica, whereas furans were higher in Arabica [27] . These differences can have a negative effect on the overall coffee flavor, as pyrazines and phenols contribute to its bitter odor [28] . The earthy odor related to pyrazines was stronger in the coffee containing higher levels of Robusta beans in blended coffee [29] .…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, Robusta showed considerably higher concentrations of pyrazines than Arabica, whereas furans were higher in Arabica [27] . These differences can have a negative effect on the overall coffee flavor, as pyrazines and phenols contribute to its bitter odor [28] . The earthy odor related to pyrazines was stronger in the coffee containing higher levels of Robusta beans in blended coffee [29] .…”
Section: Resultsmentioning
confidence: 99%